2016
DOI: 10.1007/s11666-016-0494-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Spray Parameters and Post-spray Heat Treatment on Microstructure and Mechanical Properties of Warm-Sprayed Ti-6Al-4V Coatings

Abstract: Warm spray is a novel thermal spray technique that allows the formation of dense and relatively pure Ti-6Al-4V coatings due to its capability to control the temperature of the propellant gas by diluting the combustion flame with an inert gas such as nitrogen. Recently, its combustion pressure has been increased from 1 to 4 MPa aiming to further increase particle velocity to over 1000 m/ s. Two series of coatings with combustion pressure of 1 and 4 MPa and various nitrogen flow rates were prepared in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…It should also be noted that no oxidation was observed in Al coatings, even for the highest process temperature ( Figure 4 a (Al_1.0)). The above observations, especially for Ti, are consistent with our previously published results [ 30 , 31 , 32 ]. The dense and uniform Al coatings are more suitable for better corrosion resistance, unlike the porous and oxidized Ti depositions.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It should also be noted that no oxidation was observed in Al coatings, even for the highest process temperature ( Figure 4 a (Al_1.0)). The above observations, especially for Ti, are consistent with our previously published results [ 30 , 31 , 32 ]. The dense and uniform Al coatings are more suitable for better corrosion resistance, unlike the porous and oxidized Ti depositions.…”
Section: Resultssupporting
confidence: 93%
“…As described during the microstructure analysis, these changes are derivative of two independent phenomena occurring during coating deposition (i.e., strain hardening and thermal softening). The mutual contribution of these phenomena, being a derivative of the WS temperature, which is a function of the NFR parameter, determines the coating microstructure (i.e., porosity, oxidized area) and mechanical properties (e.g., hardness) [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, a study by Molak et al [16] also reported good results after heat treating Ti-6Al-4V coatings deposited by warm spray thermal technique. They sprayed coatings at different pressures, from 1 to 4 MPa, and controlling the temperature of the propellant gas by diluting the combustion flame with nitrogen.…”
Section: Introductionmentioning
confidence: 94%
“…In another investigation, Molak et al [44] studied the effects of post-spray heat treatment and spray parameters on mechanical properties and microstructure of warm-sprayed Ti-6Al-4V coatings on low carbon steel (JIS: SS 400). Results showed that spray parameters affect both the oxygen content and porosity of the coatings.…”
Section: Hvof Spray Coatingmentioning
confidence: 99%